Corporate Criminal Liability in Corporate Crime Cases: Legal Review and Policy Implications - Imanuddin, Iman; Aringga, Rino Dedi (Jurnal Ar Ro'is Mandalika (Armada), 2025)
With an emphasis on Indonesia's legal system and policy ramifications, this study examines corporate criminal liability in corporate crime cases. The law acknowledges corporate liability, but enforcement is still limited, according to a review of the literature and a case analysis. Proving law enforcement's ability and intent is one of the main obstacles. Therefore, in order to improve corporate accountability, comprehensive policy reform is required, which includes strengthening whistleblowing, international collaboration, improving legislation, increasing resources, and increasing transparency.